Determinants and measures to assess farmers’ participation in Participatory Irrigation Management (PIM) at the tail-end of irrigation schemes in Sri Lanka : a review of the empirical evidence - Yapa, LGDS; Anisah Lee Abdullah; Ruslan Rainis; Hemakumara, GPTS (Penerbit Universiti Kebangsaan Malaysia, 2022)
Assessing the determinants affecting farmers’ participation in Participatory Irrigation Management (PIM) at the farm household level is vital in identifying the root causes of the prevailing problems at the tail-end of irrigation schemes in Sri Lanka, with a view to finding national level remedies to solve the head-tail disparities in sharing water. The main objective of this study is to propose appropriate determinants and measures to assess farming practices in PIM in Sri Lanka while reviewing the spatial and non-spatial factors that affect, whether significantly or otherwise, farmers’ participation in collective activities. A systematic literature review was conducted using PRISMA guidelines. A total of 28 full-text research articles on farmers’ participation in collective action were identified to propose determinants and measures to assess farmers’ participation in PIM. This study identified significant social, economic, managerial, institutional, locational, and physical factors based on previous studies. Addressing the knowledge gap, this study suggests 36 determinants that are helpful to assess the level of farmers’ participation in PIM in Sri Lanka. These include 10 social factors, 6 economic factors, 4 management factors, and 7 institutional factors under the non-spatial category, while 5 of the locational and 4 of the physical factors fall under the spatial category. Moreover, this study ensures consistency between the different measures applied to assess farmers’ participation and recommends the usage of distributional and proportional measures to determine farmers’ participation in PIM in Sri Lanka as well as in other countries where IMT or PIM is being implemented.